Immunomodulator FTY720 improves glucose homeostasis and diabetic complications by rejuvenation of β‐cell function in nonhuman primate model of diabetes. (2nd February 2022) - Wang, Yixin (Jim); Wang, Xiaoli; An, Annie; Zang, Mingfa; Xu, Ling; Gong, Kefeng; Song, Weihua; Li, Qing; Lu, Xiaojun; Xiao, Yong‐Fu; Yu, Guoliang; Ma, Zhongmin A.
Abstract: Inadequate β ‐cell mass is essential for the pathogenesis of type 2 diabetes (T2D). Previous report showed that an immunomodulator FTY720, a sphingosine 1‐phosphate (S1P) receptor modulator, sustainably normalized hyperglycemia by stimulating β ‐cell in vivo regeneration in db/db mice. We further examined the effects of FTY720 on glucose homeostasis and diabetic complications in a translational nonhuman primate (NHP) model of spontaneously developed diabetes. The male diabetic cynomolgus macaques of 18–19 year old were randomly divided into Vehicle (Purified water, n = 5) and FTY720 (5 mg/kg, n = 7) groups with oral gavage once daily for 10 weeks followed by 10 weeks drug free period. Compared with the Vehicle group, FTY720 effectively lowered HbA1c, blood concentrations of fasting glucose (FBG) and insulin, hence, decreased homeostatic model assessment of insulin resistance (HOMA‐IR); ameliorated glucose intolerance and restored glucose‐stimulated insulin release, indicating rejuvenation of β ‐cell function in diabetic NHPs. Importantly, after withdrawal of FTY720, FBG, and HbA1c remained at low level in the drug free period. Echocardiography revealed that FTY720 significantly reduced proteinuria and improved cardiac left ventricular systolic function measured by increased ejection fraction and fractional shortening in the diabetic NHPs. Finally, flow cytometry analysis (FACS) detected that FTY720 significantly reduced CD4 + and CD8 + T lymphocytes as well as increased DC cells in the circulation. Immunomodulator FTY720 improves glucose homeostasis via rejuvenation of β ‐cell function, which can be mediated by suppression of cytotoxic CD8 + T lymphocytes to β ‐cells, thus, may be a novel immunotherapy to reverse T2D progression and ameliorate the diabetic complications.